Methodology for characterising microlayers in historical plasterwork. (15th September 2015) - Blasco-López, F.J.; Alejandre, F.J.; Flores-Alés, V.
Highlights: A methodological sequence is proposed for the comprehensive study of plasterwork microlayers. Data thus obtained can be conclusive in the decisión-making for restoration interventions. Microlayer characterization and dating are useful to confirm chronological hypotheses. This case study on plasterwork from the Real Alcázar (Seville, Spain) has confirmed the method's validity. Abstract: The study of (micro)layer structure in walls is a fundamental tool for expanding our knowledge of historical buildings and developing suitable proposals for intervention and restoration. In materials such as plasterwork, the (micro)layer sequence can be confusing, resulting in the need for a more detailed analysis in order to accurately determine the materials and interventions carried out on a given decorative element in the past. This work presents a methodological proposal based on optical microscopy, XRD, micro-XRD, SEM-EDAX, FTIR, and 14 C dating to accurately identify the structure and composition of the different types of microlayers comprising the plasterwork. The resulting data are of great use in decision-making for restoration and can be compared with historiographic information in order to confirm hypotheses or clarify gaps in chronological adscription.